Comparative analysis of bacterial abundance and diversity in tumour tissue of oral squamous cell carcinoma and non-tumour tissue: insights from a systematic review of 16S ribosomal RNA sequencing - Swagatika Mohapatra; Swagatika Panda; Neeta Mohanty; Bibhu Prasad Mishra (BMC Oral Health)
Abstract Background As per the recent research findings, there is a significant difference between the bacteriome of normal tissue (NT) and tumor tissues (TT) of oral squamous cell carcinoma (OSCC). Identifying this distinct bacteriome is crucial for understanding their potential contribution to oral carcinogenesis. This systematic review (SR) aims to identify exclusive and relative bacterial abundance and bacterial diversity in TT and NT. Methodology The review was conducted following the PRISMA guidelines. PUBMED and SCOPUS databases were searched for studies in English published till 31st August 2024. The inclusion criteria focused on identifying bacteriome in NT versus TT at either species,/genus, and/or phylum level through 16 s ribosomal RNA sequencing. Quality assessment was performed using an eleven-parameter tool combining the Newcastle–Ottawa Scale and customized criteria. Result Evaluating the selected 13 articles, we have identified the exclusive and relative abundance of bacteriome in TT and NT at phylum, genus, and species levels. Three phyla such as Chloroflexota, Deinococcus-Thermus, and Mycoplasmatota, are found exclusively in TT. Seven genus such as Eubacterium, Campylobacter, Aeromonas , Oceanivigra , Rheinheimera , Weissella, and Catonella are exclusively found in TT. Ten species such as Micrococcus luteus , Prevotella melaninogenica , Exiguobacterium oxidotolerans, Fusobacterium naviforme, Staphylococcus aureus, Veillonella parvula, Parvimonas sp oral taxon 110, Eubacterium II G1 infirmum , Eubacterium XI G3 Brachy, Weissella viridescens are found in TT. Six genus such as Capnocytophaga , Selenomonas , Leptothrix , Desulfovibrio , Desulfoplanes , Pelospora are found exclusively in NT. Eleven species, such as Streptococcus sp. Oral taxon 071,Selenomonas sputigena, Treponema pedis , Acholeplasmatales bacterium, Capnocytophaga haemolytica , Eubacterium sp., Syntrophomonadaceae genomosp.,Treponema putidum , Mitsuokella sp., Actinomyces sp. Oral taxon 848 str. F0332, p- 2534 - 18B5-gut-group are found in NT. Seven common genera within which different species are identified in TT and NT, suggesting differences in bacterial behaviour and characteristics within the same genus. A total of 12 phyla, 35 genera, and 54 species were found to be relatively more abundant in TT compared to NT. Conversely, 7 phyla, 32 genera, and 45 species were relatively more abundant in NT than in TT. Considerable variations in diversity metrics were found between TT and NT. Conclusion This systematic review is the first to identify a distinct bacteriome exclusive to OSCC tumour tissue compared to normal tissue using 16S ribosomal RNA sequencing. This pioneering work lays the foundation for future studies on the oral microbiome as a potential diagnostic or therapeutic target in oral cancer management. It emphasizes the importance of exploring species-level differences for a deeper understanding of their roles in OSCC. Trial registration Not applicable.